Stunting dan Keragaman Pangan pada Balita Usia 24-59 Bulan di Indonesia (Analisis Data Indonesian Family Life Survey Tahun 2014-2015): Stunting and Dietary Diversity in Children 24-59 Months in Indonesia (Analysis of Indonesian Family Life Survey 2014-2015) - Hariawan, Muhammad Hafizh; Hasanbasri, Mubasysyir; Arjuna, Tony (Amerta Nutrition, 2024)
Background: Stunting is impaired growth and cognitive development that could decrease learning ability and productivity and increase morbidity and mortality. In 2018, 30.8% of children under the age of five in Indonesia were stunting. Chronic lack of nutrition as a cause of stunting is well known. However, the type of food that causes differences in the conditions between stunting and non-stunting children still needs further investigation. Dietary diversity is an indicator to identify the type and quality of food consumed. Objectives: Analyzing the relationship between dietary diversity and stunting and determinants of stunting in children aged 24-59 months in Indonesia. Methods: This was an observational study using a cross-sectional design. Secondary data from the (IFLS) 5 was used. Bivariate analysis was conducted using the chi-square test. Multivariate analysis used the logistic regression test. The subjects in this study were 2421 children aged 24-59 months. Results: Bivariate analysis showed a significant relationship between dietary diversity and stunting. Significant relationships were found between meat, eggs, milk and its products, and vitamin A-rich vegetables and stunting. Multivariate analysis showed LBW, economic status, area of residence, and maternal education are predictors of stunting. Conclusions: Dietary diversity, especially consumption of animal protein such as eggs, meat, fish, and milk could improve the quality of children’s diets. Improving the quality of diets could potentially reduce the risk of stunting. Therefore, efforts and strategies are needed to increase accessibility to various foods and increase nutritional knowledge.